Synergistic attenuation of complete freund’s adjuvant-induced inflammation in mice using shinbaro-pelubiprofen: a novel therapeutic complex - Hyunseong Kim; Jin Young Hong; Wan-Jin Jeon; Hyun Kim; Changhwan Yeo; Junseon Lee; Yoon Jae Lee; In-Hyuk Ha (Molecular Medicine)
Abstract Background Inflammation is a critical protective response in the body, essential for combating infections and healing injuries. However, chronic inflammation can be harmful and significantly contribute to the development and progression of chronic diseases, with macrophage-mediated responses being central to these processes. This study presents “SBR-Pel,” a new therapeutic blend of Shinbaro tab (SBR), a traditional herbal formula, and pelubiprofen (Pel), a non-steroidal anti-inflammatory drug, and investigated their combined anti-inflammatory effects to create a treatment that both improves efficacy and reduces side effects. Methods To this end, we performed both in vitro and in vivo analyses, utilizing a mouse model of inflammation. Viability and cytotoxicity assays, immunohistochemistry, enzyme-linked immunosorbent assays, real-time polymerase chain reaction assays, nociception assays, writhing tests, and blood biochemical analyses were performed. Results In vitro, SBR-Pel synergistically reduced the production of nitric oxide and reactive oxygen species and the expression of pro-inflammatory cytokines. SBR-Pel also significantly attenuated paw edema in vivo in a Complete Freund’s adjuvant-induced inflammation model in adult mice. Furthermore, immunohistochemical analyses showed that treatment with SBR-Pel reduced both the infiltration of CD68+ macrophages and the expression of pro-inflammatory cytokines in inflamed tissues. Additionally, compared with individual treatment alone, SBR-Pel enhanced the expression of anti-inflammatory cytokines CD206, TGF-β, and IL-10, indicating a synergistic effect. Our research demonstrates that SBR-Pel effectively diminishes inflammatory pain by reducing macrophage infiltration and pro-inflammatory cytokine secretion. Additionally, while 1.5 mg/kg of Pel alone increases levels of liver and kidney toxicity markers, such as aspartate aminotransferase, alanine aminotransferase, and creatinine, combining it with SBR at a reduced dosage of 0.5 mg/kg maintains these markers at normal levels. Conclusions This combined effect highlights SBR-Pel’s potential as an effective treatment for inflammatory diseases driven by heightened macrophage activity, while also minimizing side effects by reducing the Pel dosage.